High‐Salt Diet‐Induced Gastritis in C57BL/6 Mice is Associated with Microbial Dysbiosis and Alleviated by a Buckwheat Diet. Issue 8 (16th February 2020) - Li, Ya; Li, Wen; Wang, Xiao; Ding, Chao; Liu, Junze; Li, Yan; Li, Wenjuan; Sun, Yundong
Abstract : Scope: A high‐salt diet is a cause of gastritis, but the associated mechanism remains unclear. Recent studies have shown that gastric flora is associated with a variety of stomach diseases, but it is not known whether gastric flora is involved in gastritis induced by a high‐salt diet. Methods and results: Gastritis is successfully induced in C57BL/6 mice fed a high‐salt diet (salt: 5% NaCl) for four weeks. Through 16S rRNA gene sequencing, the composition of the stomach microbiota of mice fed normal and high‐salt diets are compared, the results of which show that the high‐salt diet induces significant changes in the gastric flora. Phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) is used to predict the function of the microbiota in the stomach of mice, and the results indicate that a high‐salt diet leads to a decrease in the ability of the gastric microbiota to metabolize polysaccharides and vitamins. A buckwheat diet is used to treat gastritis. The results show gastritis induced by the high‐salt diet is significantly alleviated, and the dysbiosis in the stomach also improved. Conclusion: Buckwheat diet may be one of the ways to prevent and treat gastritis caused by a high‐salt diet. Abstract : A high‐salt diet is a cause of gastritis, but the associated mechanism remains unclear. Herein, gastritis is successfully induced in C57BL/6 mice and it is found that a high‐salt diet induces gastric dysbiosis. Feeding mice with buckwheat alleviates gastritis and improves flora. Buckwheat diet may be one of the ways to prevent and treat gastritis caused by a high‐salt diet.